Kinerja Organisasi Pemerintah Daerah Dalam Implementasi Teknologi dan Dampak Terhadap Perubahan Sosial Budaya di Era Globalisasi - Jannah, Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Globalization has brought significant changes in various aspects of life, including in the governance system. This study aims to analyze the performance of local government organizations in the implementation of technology and its impact on social and cultural changes. Using a literature review approach, this research collects and analyzes various relevant literature sources, including academic journals, books, and research reports. The results of the analysis indicate that local governments face various challenges, such as budget constraints for investing in information technology infrastructure and a lack of technical skills among staff. Nevertheless, small initiatives such as the use of mobile applications for public issue reporting show potential for improving service efficiency. This study also identifies key factors influencing the successful implementation of technology in local government operations, as well as the importance of innovation to meet the demands of increasingly critical citizens. These findings are expected to provide insights for policymakers in formulating more effective strategies to address the challenges of globalization